Cross-National Comparisons of Earnings and Income Inequality - Gottschalk, Peter; Smeeding, Timothy M. (Journal of Economic Literature, 1997)
This article reviews the evidence on cross-national comparisons of earnings and income inequality in OECD countries. It begins with a series of stylized facts which are then examined and supported by recent studies in the field. Economic, demographic, institutional and policy-related influences on earnings and income distribution are reviewed. The paper concludes with a call for more work on empirically testable structural models of household income distribution.